L'île et l'archipel chez Erik Orsenna - Outeirinho, Maria de Fátima (2015)
The works of Erik Orsenna, Deux étés (1997) and The Company of the Indies (2012) allow, in various ways, exploring the role of the island, inscribed on a personal and collective mythography or even on historical mythography. In fact, the approach of these two works can be carried out independently, considering the symbolic values of the island in each fictional universe, as applicable with pseudo-autobiographical or pseudo-biographical shortcuts, but rather a relational approach in the overall context of the work of Orsenna is relevant, connected with a conception of literary creation in archipelago where each book is presented as an island located in the main sea, to regain the etymological source of the term. Thus, our main goal in this paper is to reflect, on the one hand, on the functioning of the island in the diegetic universe of the two works cited above and, secondly, to consider the heuristic contributions of the archipelago concept regarding the formation of networks of communication between the islands.